2017
DOI: 10.1681/asn.2016111179
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of C5a Receptor Inhibitor Avacopan in ANCA-Associated Vasculitis

Abstract: Alternative C activation is involved in the pathogenesis of ANCA-associated vasculitis. However, glucocorticoids used as treatment contribute to the morbidity and mortality of vasculitis. We determined whether avacopan (CCX168), an orally administered, selective C5a receptor inhibitor, could replace oral glucocorticoids without compromising efficacy. In this randomized, placebo-controlled trial, adults with newly diagnosed or relapsing vasculitis received placebo plus prednisone starting at 60 mg daily (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
273
0
26

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(321 citation statements)
references
References 36 publications
5
273
0
26
Order By: Relevance
“…Our finding of elevated levels of C5 is of particular significance given the recent success of a clinical trial using CCX168 (Avacopan) to treat ANCA-associated vasculitis 9,21 .…”
Section: Molecular Analysis Of Cerebrospinal Fluid (Csf) Is a Compellmentioning
confidence: 72%
See 1 more Smart Citation
“…Our finding of elevated levels of C5 is of particular significance given the recent success of a clinical trial using CCX168 (Avacopan) to treat ANCA-associated vasculitis 9,21 .…”
Section: Molecular Analysis Of Cerebrospinal Fluid (Csf) Is a Compellmentioning
confidence: 72%
“…More specifically, we observe significant alteration of several regulatory components of the alternative pathway, and elevated levels of the terminal cascade including complement C5 (C5), complement C8 (C8) and complement C9 (C9). In previous studies C5 has been shown to be a therapeutically relevant target for systemic Anti-Neutrophil Cytoplasmic Antibody (ANCA) vasculitis, and recent clinical trials of C5 inhibitors further support this notion 9 . Our results suggest a rationale for investigating whether C5 inhibitors could serve as a novel therapy for PACNS.…”
Section: Molecular Analysis Of Cerebrospinal Fluid (Csf) Is a Compellmentioning
confidence: 91%
“…Avacopan, previously called CCX168, is an orally administered small-molecule C5aR antagonist that blocks the effects of C5a and prevented the development of GN induced by anti-myeloperoxidase antibodies in a murine model of ANCA associated vasculitis (AAV) [37]. Jayne et al [38] recently studied the drug as a potential steroid-sparing agent in the treatment of this disease. Sixty-seven patients (mean age 58, GFR at baseline 50 mL/min; patients with severe systemic involvement like pulmonary hemorrhage or cerebral vasculitis were excluded) were randomized into 3 arms.…”
Section: Current Therapy For Anca-positive Rpgnmentioning
confidence: 99%
“…Adverse effects were lower in the experimental arms. Better quality of life scores and less new onset or worsening diabetes was seen as well with avacopan [38]. The ongoing ADVOCATE study (NCT 02994927) will look at using this drug to completely replace glucocorticoids in patients with more severe renal ANCA disease.…”
Section: Current Therapy For Anca-positive Rpgnmentioning
confidence: 99%
“…(El Karoui et al, 2012) In anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis, C5a and C5a receptor (C5aR/CD88) play a key pathogenetic role. (Furuta and Jayne, 2013;Halbwachs and Lesavre, 2012;Jayne et al, 2017;Kettritz, 2014) C5a, acting on the C5aR is a potent neutrophil chemoattractant. (Hammerschmidt et al, 1981) In the presence of ANCA, C5a can lead to a decrease in neutrophil deformability, which in turn slows their ability to migrate across small blood vessels.…”
Section: Complement Dysregulation Is Central To Thrombotic Microangiomentioning
confidence: 99%